Interstellar gas towards CTB 37A and the TeV gamma-ray source HESS J1714−385 - Maxted, N.; Rowell, G.; Dawson, B.; Burton, M.; Fukui, Y.; Walsh, Andrew; Kawamura, A.; Horachi, H.; Sano, H.; Yoshiike, S.; Fukuda, T. (Oxford University Press, 2013)
Observations of dense molecular gas towards the supernova remnants CTB 37A (G348.5+0.1) and G348.5−0.0 were carried out using the Mopra and Nanten2 radio telescopes. We present CO(2–1) and CS(1–0) emission maps of a region encompassing the CTB 37A TeV gamma-ray emission, HESS J1714−385, revealing regions of dense gas within associated molecular clouds. Some gas displays good overlap with gamma-ray emission, consistent with hadronic gamma-ray emission scenarios. Masses of gas towards the HESS J1714−385 TeV gamma-ray emission region were estimated, and were of the order of 103–104 M. In the case of a purely hadronic origin for the gamma-ray emission, the cosmic ray flux enhancement is ~80–1100 times the local solar value. This enhancement factor and other considerations allow a discussion of the age of CTB 37A, which is consistent with ~104 yr.